GLOBALIZATION AND THE SPREAD OF THE ENGLISH LANGUAGE - XIDIROVA MOHINUR SHUHRAT QIZI (TADQIQOTLAR, 2025)
Abstract This  article  provides  an  in-depth  examination  of  how  globalization  has facilitated  the  global  spread  of  the  English  language.  It  investigates  the  historical evolution of English dominance from the colonial era to the digital age, emphasizing the  economic,  cultural,  political,  and  technological  forces  that  have  shaped  its international status. The article also evaluates the consequences of English expansion for linguistic diversity, cultural identity, and global communication. Furthermore, it explores  the  rise  of  'World  Englishes,'  the  transformation  of  English  into  a  global resource rather than the property of native speakers, and the challenges this creates for education systems around the world. The study concludes by stressing the importance of multilingualism in preserving cultural heritage while benefiting from the advantages English provides in a globalized society.